Estudos ecológicos sobre a decomposição de serapilheira em vegetacão de cerrado - Silva, Laura Vívian Barbosa (2009)
In most ecosystems, 50 to 80% of the soil nutrients are originated from litter decomposition. The rate of litter decomposition is affected mostly by the environmental conditions, litter quality and the decomposer community. However, there are other factors that can influence on litter decomposition. The aim of this study was (a) to determine experimentally the effects of increased nitrogen deposition on litter decomposition and, (b) determine if there is a relationship between plant palatability to leaf-cutter ants and litter decomposition. The rate of decomposition was estimated using litterbags containing 10g of leaf litter. These litterbags were distributed on the soil surface in two types of cerrado (savanna) in the Estação Ecológica do Panga in October 2007. The dead leaves of the species were dried and weighed to determine the fraction of leaf mass remaining. To investigate the effect of N deposition on decomposition, litterbags were distributed in 15 plots in cerrado ralo among three treatments: control, high N and low N input. To evaluate the relationship between plant palatability to leafcutter ants and litter decomposition, decay rate was compared between highly palatable and poorly palatable species in an area of cerrado denso. Initial concentrations of N, P e lignin were measured from the leaves of the species studied to compare the initial nutrient contents, .and to analyze the dynamics of nutrients during the decomposition process. Soil N addition did not affect litter decomposition for none of the three species studied, although they did differ in the concentration of N, P and lignin. This suggests that eventual changes caused in the availability of soil N to the decomposer community were not strong enough to affect decomposition. Overall, there was no significant relationship between plant palatability to leaf-cutter ants and litter decomposition. This may be explained because litter decomposition was correlated with P concentrations, and these did change according to plant palatability to leaf-cutter ants. Highly palatable plants presented a higher concentration of N and a lower lignin:N ratio. However, neither of these parameters were good predictors of litter decomposition for the species studied.